Державна політика регулювання доходів в умовах підвищення фіскальних ризиків, спричинених пандемією covid-19 - Zhebchuk, Roman; Popadynets, Nazariy (West Ukrainian National University, 2021)
Зазначено високу залежність бюджетних надходжень від податкової та боргової політик, зростання їх ролі в умовах економічного спаду. Наголошено на необхідності та важливості розроблення тактики та стратегії бюджетної та податкової політик, а також можливості їх гнучкої зміни в умовах непередбачуваних спадів в економіці. Вказано на необхідність у державній політиці доходів враховувати фіскальні стимули та фіскальну децентралізацію. Приділено увагу можливостям і загрозам, які породжує поглиблення процесів децентралізації в Україні, акцентовано увагу на складових фінансової спроможності територіальних громад та достатності фінансових ресурсів. Акцентовано увагу на тому, що територіальний перерозподіл коштів повинен враховувати вимоги найбільш раціонального розміщення продуктивних сил, сприяти веденню бізнесу, розв’язувати суперечності, які виникають у процесі балансування доходів бюджету та конституційних соціальних зобов’язань. Процеси децентралізації бюджетних та податкових відносин повинні супроводжуватися посиленням їх соціальної орієнтації. Зазначено, що фінансова грамотність населення грає значну роль в зниженні рівня емоційних потрясінь під час економічних спадів. Запропоновано гіпотезу для подальших наукових пошуків щодо залежності ефективності політики децентралізації владних повноважень від використання на регіональному рівні сучасних підходів до фінансового управління, що вимагатиме імплементації інноваційних регуляторних важелів управління змінами. Зокрема, запропоновано реалізацію низки заходів з виявлення та протидії ризикам дестабілізації як основи для забезпечення фінансово-економічної безпеки держави. Наголошено на необхідності подальшого вдосконалення інституційної координації застосування регіональних регулятивних податково-бюджетних інструментів і механізмів з національними й міжнародними нормами і правилами. Зазначено, що в умовах карантинних обмежень через пандемією COVID-19, реалізація комплексу заходів податково-бюджетної підтримки громадян, малого та середнього бізнесу повинна здійснюватися відповідно до чітко сформульованої та затвердженої програми, яка має бути розроблена з урахуванням оцінки ризиків та не мати ситуативного характеру.
State policy of income regulation in the conditions of increasing fiscal risks caused by the covid-19 pandemic
Introduction. Today, in the conditions of the COVID-19 pandemic, a number of economic problems have arisen in the country, which can be prevented by improving revenue policy. As the revenue part is formed in the current conditions of the budget decentralization reforms, the risks arising during the pandemic have become an important challenge for the entire economic system of the state and each territorial community in particular. The purpose of the article is to highlight current issues of state regulation of the domestic economy related to global economic challenges and fiscal risk management caused by the COVID-19 pandemic. Results. The high dependence of budget revenues on tax and debt policies, the growth of their role in the economic downturn are analyzed. Emphasis is placed on the need and importance of developing tactics and strategies for budget and tax policies, as well as the possibility of their flexible change in the face of unpredictable economic downturns. The need for state revenue policy to take into account fiscal incentives and fiscal decentralization is indicated. Particular attention is paid to the opportunities and threats posed by the deepening of decentralization processes in Ukraine, emphasis is placed on the components of the financial capacity of local communities and the adequacy of financial resources. It was mentioned that the territorial redistribution of funds must take into account the requirements of the most rational allocation of productive forces, promote business, resolve conflicts that arise in the process of balancing budget revenues and constitutional social obligations. Processes of decentralization of budgetary and tax relations should be accompanied by strengthening of their social orientation. It is noted that the financial literacy of the population plays a significant role in reducing the level of emotional turmoil during economic downturns. At the same time, the study proposed a hypothesis for further research about the dependence of the effectiveness of decentralization policy on the use of modern approaches to financial management at the regional level, which require the implementation of innovative regulatory levers for change management. Conclusions. A number of conclusions and recommendations were formulated. In particular, it is proposed to implement a number of measures to identify and counter the risks of destabilization as a basis for ensuring the financial and economic security of the state. The need to further improvement of the institutional coordination of the application of regional regulatory fiscal instruments and mechanisms with national and international norms and rules was emphasized. It was noted that in the conditions of quarantine restrictions due to the COVID-19 pandemic, the implementation of a set of measures of tax and budget support for citizens, small and medium businesses should be carried out in accordance with a clearly defined and approved program.
Keywords: фіскальна політика; бюджетна політика; COVID-19; децентралізація